How Intellectual Capital and Governance Shape Firm Performance: Evidence from Indonesia’s Energy Sector - Diah Sulistiani; Nurcahyono; R Ery Wibowo Agung Santosa (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
Amid increasing pressure on firms to enhance financial performance while addressing sustainability and governance challenges, energy sector companies face heightened scrutiny due to their capital intensity, environmental impact, and complex operational structures. This study examines the impact of intellectual capital, environmental performance, and capital structure on corporate financial performance, while investigating the moderating role of independent commissioners. The sample comprises energy sector firms listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period, yielding 236 firm-year observations selected through purposive sampling. Secondary data were obtained from annual reports and analyzed using panel data regression with EViews 13. The findings reveal that intellectual capital exerts a positive and significant impact on financial performance, whereas environmental performance and capital structure show no significant effect. Furthermore, the independent board of commissioners strengthens the relationship between intellectual capital and financial performance but does not moderate the effects of environmental performance or capital structure. These results underscore the strategic importance of intangible assets and governance mechanisms in enhancing firm performance, while highlighting the need for stronger integration of environmental initiatives and capital structure decisions into business models to achieve sustainable economic value.